Potential antifungal targets based on histones post-translational modifications against invasive aspergillosis - Li, Yiman; Song, Zhihui; Wang, Ente; Dong, Liming; Bai, Jie; Wang, Dong; Zhu, Jinyan; Zhang, Chao (Frontiers in Microbiology, 2022)
As a primary cause of death in patients with hematological malignancies and transplant recipients, invasive aspergillosis (IA) is a condition that warrants attention. IA infections have been increasing, which remains a significant cause of morbidity and mortality in immunocompromised patients. During the past decade, antifungal drug resistance has emerged, which is especially concerning for management given the limited options for treating azole-resistant infections and the possibility of failure of prophylaxis in those high-risk patients. Histone posttranslational modifications (HPTMs), mainly including acetylation, methylation, ubiquitination and phosphorylation, are crucial epigenetic mechanisms regulating various biological events, which could modify the conformation of histone and influence chromatin-associated nuclear processes to regulate development, cellular responsiveness, and biological phenotype without affecting the underlying genetic sequence. In recent years, fungi have become important model organisms for studying epigenetic regulation. HPTMs involves in growth and development, secondary metabolite biosynthesis and virulence in Aspergillus. This review mainly aims at summarizing the acetylation, deacetylation, methylation, demethylation and sumoylation of histones in IA and connect this knowledge to possible HPTMs-based antifungal drugs. We hope this research could provide a reference for exploring new drug targets and developing low-toxic and high-efficiency antifungal strategies.